2002
DOI: 10.2166/ws.2002.0003
|View full text |Cite
|
Sign up to set email alerts
|

Residue-free removal of arsenic, iron, manganese and ammonia from groundwater

Abstract: The paper presents a residue-free kind of water treatment process for the removal of metals like arsenic, iron and manganese and other water constituents like ammonia which may deteriorate drinking water quality. In this process the underground body, i.e. the aquifer, is used as a natural reactor. The results of field experiments of two technical-scale in-situ groundwater treatment plants are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Especially at low to moderate arsenic concentrations, the technology of arsenic adsorption is relatively effective. A new approach to remove arsenic from groundwater is by retention in the subsurface, because during in-situ or subsurface iron removal, arsenic levels are also reduced (Rott and Meyer, 2002;van Halem et al, 2008). At many groundwater treatment plants in Europe, incidental co-precipitation of arsenite and arsenate occurs during iron removal.…”
Section: Arsenic Not a Problem In Europe?mentioning
confidence: 99%
“…Especially at low to moderate arsenic concentrations, the technology of arsenic adsorption is relatively effective. A new approach to remove arsenic from groundwater is by retention in the subsurface, because during in-situ or subsurface iron removal, arsenic levels are also reduced (Rott and Meyer, 2002;van Halem et al, 2008). At many groundwater treatment plants in Europe, incidental co-precipitation of arsenite and arsenate occurs during iron removal.…”
Section: Arsenic Not a Problem In Europe?mentioning
confidence: 99%
“…Groundwater arsenic concentrations were not reported in this publication, but the surrounding wells had concentrations exceeding 500 µg l −1 . Arsenic removal during subsurface treatment has also been observed by Rott et al (2002), reducing arsenic concentrations from 38 µg l −1 to below 10 µg l −1 after repeating the process 20 times. Van Halem et al (2010b) found less encouraging results at sites in Bangladesh with 145 µg l −1 arsenic, with immediate arsenic breakthrough upon abstraction (V i = 1 m 3 ).…”
Section: Introductionmentioning
confidence: 91%
“…In contrast, the in situ arsenic removal is a relatively new venture (Rott et al, 2002;van Halem et al, 2009). Nevertheless, the in situ arsenic removal has potentially been developed as a costeffective method to provide safe drinking water for rural and remote areas.…”
mentioning
confidence: 99%
“…Nevertheless, the in situ arsenic removal has potentially been developed as a costeffective method to provide safe drinking water for rural and remote areas. It has been reported that injecting aerated water into an aquifer reduced the concentration of arsenic from as high as 400 μg/L to the WHO standard (≤ 10 μg/L) (Appelo and de Vet, 2003;Rott et al, 2002). In Bangladesh, Sarkar and Rahman (2001) reported that using this method can lower high concentrations of arsenic (500-1300 μg/L) by more than 50%.…”
mentioning
confidence: 99%